2014
DOI: 10.1038/bmt.2014.63
|View full text |Cite|
|
Sign up to set email alerts
|

Endocrine, metabolic, nutritional and body composition abnormalities are common in advanced intensively-treated (transplanted) multiple myeloma

Abstract: Modern treatment strategies have increased life expectancy in multiple myeloma, but little is known about the endocrine, metabolic and nutritional status of long-term survivors. We performed endocrine, metabolic, bone, body composition and nutritional evaluations in 32 patients with intensively-treated, advanced but stable, myeloma a median duration of 6 years from diagnosis and three lines of intensive treatment, including at least one haematopoietic SCT procedure. All patients were off active treatment. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…This results in the anti-proliferative and anti-tumorigenic effects of adiponectin observed in MM, breast, prostate, colon and liver cancers [74, 78]. Overweight and obese individuals typically present with low levels of adiponectin and are at a greater risk of developing MM when compared to individuals of healthy weight [80, 81]. Mechanistically, deficiency in adiponectin hinders the biological actions of several signaling pathways that are essential to prevent growth, proliferation, migration, and drug resistance of MM cells [81], and adiponectin can alter bone turnover for net bone anabolic or catabolic effects [82, 83].…”
Section: Myeloma Interaction With Bm Elementsmentioning
confidence: 99%
See 3 more Smart Citations
“…This results in the anti-proliferative and anti-tumorigenic effects of adiponectin observed in MM, breast, prostate, colon and liver cancers [74, 78]. Overweight and obese individuals typically present with low levels of adiponectin and are at a greater risk of developing MM when compared to individuals of healthy weight [80, 81]. Mechanistically, deficiency in adiponectin hinders the biological actions of several signaling pathways that are essential to prevent growth, proliferation, migration, and drug resistance of MM cells [81], and adiponectin can alter bone turnover for net bone anabolic or catabolic effects [82, 83].…”
Section: Myeloma Interaction With Bm Elementsmentioning
confidence: 99%
“…Overweight and obese individuals typically present with low levels of adiponectin and are at a greater risk of developing MM when compared to individuals of healthy weight [80, 81]. Mechanistically, deficiency in adiponectin hinders the biological actions of several signaling pathways that are essential to prevent growth, proliferation, migration, and drug resistance of MM cells [81], and adiponectin can alter bone turnover for net bone anabolic or catabolic effects [82, 83]. Hence the net effects of adiponectin on myeloma-induced bone disease and tumor burden remain controversial.…”
Section: Myeloma Interaction With Bm Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a median duration of 6 years from diagnosis, dual-X-ray absorptiometry identified sarcopenic obesity in 65% of patients. 39 Importantly, the development of sarcopenic obesity following HCT has yet to be independently associated with increased cardiovascular mortality. In the pediatric population, a cross-sectional study evaluating 54 allo-HCT survivors and 894 healthy participants found a deficiency in lean mass (as identified by dual-X-ray absorptiometry) as compared with fat mass in HCT survivors.…”
Section: Abdominal Obesitymentioning
confidence: 99%